Therapeutic advances in hemophilia: from molecular innovation to patient-centered global care - Dushimova, Zaure; Pashimov, Marat; Kaibullayeva, Jamilya; Danyarova, Laura; Kultanova, Elmira; Abdilova, Gulnara; Mustapayeva, Nagima (Frontiers in Medicine, 2025)
Hemophilia A and B are uncommon inherited bleeding disorders linked to the X chromosome, resulting from a lack of coagulation factors VIII or IX, respectively. Acknowledged for centuries, hemophilia was historically a dangerous condition lacking effective treatment methods. Significant progress in the 20th century brought about clotting factor alternatives and strategies for preventive treatment. This review offers a refreshed overview of both conventional and new therapies, such as gene therapy, by assessing their advantages, drawbacks, and potential future developments. The narrative review consolidates existing information regarding the pathophysiology of hemophilia, its classification, genotype–phenotype correlations, and advancements in treatment. It examines factor replacement therapies along with newer strategies like non-factor therapies, immune tolerance induction, and gene therapy, while evaluating how these treatments affect patient quality of life and worldwide access to healthcare. While factor replacement therapy is still essential, it entails regular infusions, substantial expenses, and potential risks of inhibitor formation. Innovations such as extended half-life treatments and subcutaneous therapies have enhanced adherence and lowered bleeding rates. Gene therapy has demonstrated the possibility of prolonged natural factor production but continues to encounter issues concerning long-term safety, durability, and accessibility. Newly emerging concerns include the underrepresentation of Hemophilia B in translational research, the immunological challenges associated with vector-based platforms, and significant global disparities in accessing advanced therapies, particularly in low-resource settings. In spite of progress, inequalities in treatment remain, with around 70% of patients globally unable to access crucial therapies.